FOX DOMESTICATION: MOLECULAR MECHANISMS INVOLVED IN SELECTION FOR BEHAVIOR - L. N. Trut; Yu. E. Herbeck; A. V. Kharlamova; R. G. Gulevich; A. V. Kukekova (Вавиловский журнал генетики и селекции, 2014)
Although animal domestication has enjoyed the attention of geneticists and evolutionary biologists since Darwin’s times, the focal question about genetic basis of this process has not been duly considered. We have presented here some results of experimental modeling of historical domestication in silver foxes (Vulpes vulpes), one of the object of commercial breeding. Attention is focused on the role of artificial selection in the transformation of behavior of these animals, which has created the unique populations of tame and aggressive foxes. Additional resources were developed to analyze the molecular nature of differences in the behavior of these unique foxes: the meiotic map of the fox genome was constructed, crosses of tame and aggressive animals obtained informative segregating subpopulations, and the formerly applied method of quantification of behavioral phenotypes was improved. Integrated behavioral phenotypes (principal components PC1 and PC2) used in the study were obtained by analysis of ethological parameters recorded by a camcorder. The most important result is that the region most closely associated with tame behavior was identified on fox chromosome 12 by QTL interval mapping. The result is the more so significant that the region is similar to the region on canine chromosome 5 presumed to be responsible for early domestication of wolves and their evolutionary transformation to primitive dogs.